Understanding the Structure of a Large Heroin Distribution Network: A Quantitative Analysis of Qualitative Data - Natarajan, Mangai (Journal of quantitative criminology, 2006)
An analysis is reported of 2,408 wiretap conversations gathered in the course of prosecuting a heroin dealing organization in New York City in the 1990s. The five-step analysis, which included a social network analysis of phone contacts, revealed a large, loosely structured group of 294 individuals, most of whom had very limited contacts with others in the group. The group’s active core comprised 38 individuals with extended contacts, little status differentiation and some task specialization. A smaller more tightly connected group of 22 individuals was somewhat independent of the remainder of the core and appeared to constitute a “communal business”. The existence was not confirmed of the large criminal conspiracy described by the prosecution that operated at all levels of trafficking and dealing, from wholesale distribution to street sales. Rather, it appeared that the 294 individuals comprised one segment of the heroin market in the city. However, the discrepancy could be due to the fact that the prosecution drew upon a wider set of information about the individuals concerned than provided by the wiretap data. The study supports recent analyses that see organized crimes, such as drug trafficking, as mostly the work of small groups of loosely linked entrepreneurs rather than large, highly structured criminal syndicates.